Ureteroileal bypass: a new technic to treat ureteroenteric strictures in urinary diversion - Padovani,Guilherme P. (2018)
ABSTRACT Objective: To present our technique of ureteroileal bypass to treat uretero-enteric stric- tures in urinary diversion. Materials and Methods: One hundred and forty-one medical records were reviewed from patients submitted to radical cystectomy to treat muscle-invasive bladder cancer between 2013 and 2015. Twelve (8.5%) patients developed uretero-enteric anastomotic stricture during follow-up. Five patients were treated with endoscopic dilatation and double J placement. Four were treated surgically with standard terminal-lateral im- plantation. Three patients with uretero-enteric anastomotic stricture were treated at our institution by “ureteroileal bypass”, one of them was treated with robotic surgery. Results: All patients had the diagnosis of uretero-enteric anastomotic stricture via computerized tomography and DTPA renal scan. Time between cystectomy and diag- nosis of uretero-enteric anastomotic stricture varied from five months to three years. Mean operative time was 120±17.9 minutes (98 to 142 min) and hospital stay was 3.3±0.62 days (3 to 4 days). Mean follow-up was 24±39.5 months (6 to 72 months). During follow-up, all patients were asymptomatic and presented improvement in ure-terohydronephrosis. Serum creatinine of all patients had been stable. Conclusions: Latero-lateral ureter re-implantation is feasible by open or even robotic surgery with positive results, reasonable operation time, and without complications.